STRATEGIC CULTURE AND QUALITY OF GOVERNMENT - Shedyakov, Vladimir (Collection of scientific papers «ΛΌГOΣ», 2024)
Controllability as flexibility/adaptability of the subject of management, stability of the management system, reflexivity of the management process and the configuration of various feedbacks are especially in demand by history and society at turning points of transformations. Having process understanding and strategic culture at critical points of change becomes critical. Now humanity has entered another period of discovering new horizons of life and sociocultural order, mechanisms for ensuring security and development of the ecumene [1-7]. On the one hand, the alternatives are too radical, on the other, weak influences at the bifurcation point may turn out to be decisive. A special place in the determination of rhythmicity and non-rhythmicity, cyclicality and direction of development of socio-economic integrity is occupied by forms of selective interaction. At the same time, the opportunity has been created for a more flexible and gentle reflection in the strategy of the presence of anomalous socio-economic phenomena and peripheral cultures. Fundamentally heterogeneous structures are consolidated. The leading socio-psychological motives for integration are changing. Internal values and deeply individual meanings, approaches and views of numerically small groups acquire resonance at macro levels, and sometimes are aggressively imposed on everyone. Many social trends are still just emerging, others are difficult to recognize in the sea of previous patterns and fading facts. The social need for a ban on the violent manipulation of innovations, even of the outsider type, on the destruction of even countercultural logics is objectified: the new era creates its own cultural worlds, where there is a place for everyone.